Biology and Predatory Behavior of Metioche vittaticollis (Stal) (Orthoptera: Gryllidae) - Sri Karindah; Bagyo Yanuwiadi; Liliek Sulistyowati (University of Brawijaya, 2012)
Metioche vittaticollis (Stal) is one of the generalist predator in rice field habitat. The biology and predatory behavior were studied in the laboratory. The life cycle of M. vittaticollis (Stal) averaged 40–61 days at 26°-28oC. The eggs were inserted singly within the leaf sheath of rice or weeds and hatched in 14.28 days. The nymphal period was varied between 27 and 45 days and passed four nymphal stadia. Female fecundity was averaged 50 eggs during her lifetime. The longevity of the female or male adult was ranged from 20 to 38 days. The average longevity of females and males were 29.24 and 25.00 days, respectively. The longevity of unmated female or male were longer than the mated female or male. The egg and first instar nymph sustained the high mortality of 30% and 25%, respectively, whilst there was less mortality in the third and fourth instar nymph. The adult females of M. vittaticollis survived for 32 days and the rate of survival was high in the young adults but decreased as the cricket aged. The females were more preferred to Brown Plant Hopper (BHP) nymph than the males. The early nymph stage of prey was the most stage to be fed by M. vittaticollis. However, the predation declined when they were given prey of late instar of BPH nymphs. Fewer adult stage of BPH was consumed by both male and female crickets.Key words: biology; generalist predator; prey consumption; Metioche vittaticollis